ANALYSIS OF BOILER MACHINERY MAINTENANCE USING OEE (OVERALL EQUIPMENT EFFECTIVENESS ) METHOD IN TAHU ASIN SINAR BANDUNG FACTORY - Gusniar, Iwan Nugraha; Sandy, Rio (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
The boiler engine is one of the strategies in increasing the efficiency of energy use, especially in the process of making tofu, the boiler works as a chemical (potential) energy conversion engine from fuel to heat energy in the form of steam by heating the fuel for that the boiler may always operate with optimal performance , The purpose of this study is to determine the effectiveness of the boiler machine during production, the effectiveness values include availability, performance rate and quality rate, the data analysis method is carried out with the overall method of equipment effectiveness using weekly data, after doing research, the availability value is 89.7%, The value of the performance rate is 87.9%, the engine quality rate shows a result of 99.9%, and the results of the calculation of Overall Equipment Effectiveness are 78.51%, it can be concluded that this value has not reached the standard or in other words the boiler engine needs to be reworked time management good production from wa time of machine operating availability (availability) as well as boiler engine performance from production (Performance rate) to increase the value of Overall Equipment Effectiveness.